MBCL-29. FEASIBILITY OF SCREENING AND REASONS FOR SCREENING FAILURES IN THE SIOPE PNET 5 MB TRIAL. Issue 2 (22nd June 2018) - Doz, François; Clifford, Steven; Pietsch, Torsten; Avula, Shivaram; Mynarek, Martin; Riechers, Regine; Benesch, Martin; Gerber, Nicolas U; Massimino, Maura; Sabel, Magnus; Jacobs, Sandra; Ariza, Miguel Garcia; et al.
Abstract: BACKGROUND: Current medulloblastoma treatment must take into account bio-pathological risk-categories. The ongoing European PNET 5 MB trial for standard risk medulloblastoma comprises two sub-studies: a LR (low-risk) arm for WNT-medulloblastoma and a SR (standard-risk) arm for non-anaplastic/LCA, non-WNT-medulloblastoma without MYCN or MYC amplification. Submission of frozen tumor sample is mandated for this biomarker-based patient stratification. Pre-screening also includes pathological and imaging review. METHODS: We investigated all pre-screened standard-risk medulloblastoma patients (i.e. excluding those diagnosed locally with residual or metastatic disease*) and reasons for non-inclusion in the LR or SR arm. RESULTS: 235 standard-risk medulloblastoma patients from 11 countries were pre-screened. Reasons for non-inclusion (130) were: imaging review demonstrating metastatic disease (12*), or surgical residue above 1.5 cm 2 (12), histology review demonstrating anaplastic or LCA-MB (31), unavailability of frozen tumor tissue (24), biological criteria demonstrating high risk factors MYCN or MYC amplification (17), randomization refusal in the SR-arm (13), or other (21). 105 of 235 patients (45%) of screened patients have been included into the PNET 5 MB trial per 31 Aug 2017. CONCLUSION: Histopathological review, frozen sample collection, biological pre-inclusion-assessments, and radiological review are feasible within 28 days of surgery, allowing inclusion of a comprehensively screened cohort of patients, as planned in the study. An amendment for upfront prospective subgrouping of all medulloblastoma samples, and constitutional genetic testing in SHH-MB and in WNT-MB without somatic CTNNB1 mutation will be implemented in 2018. *No results from Germany included, as reports on local assessments of metastatic disease are not yet available.